An improved coarse alignment algorithm for SINS based on rotation modulation - Yong Yang; Donglin Li; Lingbing Kong; Kaijun Xu; Honghui Xiang (AIP Advances)
Coarse alignment in strapdown inertial navigation systems (SINSs) is a critical step in ensuring initial alignment and the proper functioning of the system. The primary challenge in this process lies in reducing the alignment time while enhancing accuracy, particularly as conventional analytic algorithms often suffer from decreased precision due to measurement errors in accelerometers and gyroscopes. This paper proposes an improved coarse alignment algorithm by introducing single-axis continuous rotation modulation to compensate for the errors in gyroscopes and accelerometers, thus improving accuracy. The simulation results show that within the same alignment time, this method enhances horizontal accuracy by ∼80% compared to traditional analytic coarse alignment algorithms. The proposed approach effectively mitigates the constant bias errors of inertial sensors, significantly improving the overall alignment precision of the SINS.